Role of PDGF-A/B Ligands in Cardiac Repair After Myocardial Infarction - Kalra, Kunal; Eberhard, Joerg; Farbehi, Nona; Chong, James J.; Xaymardan, Munira (Frontiers in Cell and Developmental Biology, 2021)
Platelet-Derived Growth Factors (PDGFs) are powerful inducers of cellular mitosis, migration, angiogenesis, and matrix modulation that play pivotal roles in the development, homeostasis, and healing of cardiac tissues. PDGFs are key singaling molecules and important drug targets in the treatment of cardiovascular disease as multiple researchers have shown that delivery of recombinant PDGF ligands during or after myocardial infarction can reduce mortality and improve cardiac function in both rodents and porcine models. The mechanism involved cannot be easily elucidated due to the complexity of PDGF regulatory activities, crosstalk with other protein tyrosine kinase activators, and diversity of the pathological milieu. This review outlines the possible roles of PDGF ligands A and B in the healing of cardiac tissues including reduced cell death, improved vascularisation and improved extracellular matrix remodelling to improve cardiac architecture and function after acute myocardial injury. This review may highlight the use of recombinant PDGF-A and PDGF-B as a potential therapeutic modality in the treatment of cardiac injury.